ANALISIS KEMAMPUAN MEMBACA SISWA DALAM MEMAHAMICERITA FIKSI MELALUI MEDIA PETA CERITA DI KELAS IV SDN 13KABUPATEN SORONG - Wahyu Komalasari; Muhammad Faizin; Heny Sri Astuti (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Reading comprehension skills among elementary school students remain a significant challenge, especially in regions with limited technological resources such as Sorong Regency. This study aims to analyze the effectiveness of story map media in enhancing fiction story comprehension among sixth-grade students at SDN 13 Aimas. The method employed is descriptive qualitative research with data collection techniques including observation, reading comprehension tests, interviews, and documentation. Data analysis was conducted interactively using the Miles, Huberman, and Saldana model. Findings indicate that the use of story map media significantly aids students in understanding story elements literally and inferentially, although critical comprehension of moral messages still requires additional guidance. These results reinforce reading learning theories emphasizing the role of visual media in supporting meaning construction. In conclusion, story map media is an effective and contextual instructional strategy to improve reading literacy in elementary schools, particularly in technology-limited areas. Future research is recommended to develop digital story maps and expand subject coverage for broader generalization.